THU0492 Macrophage activation syndrome as the initial manifestation of juvenile systemic lupus erythematosus. (15th June 2017) - Sato, S; Uejima, Y; Suganuma, E; Takano, T; Fujinaga, S; Kawano, Y
Abstract : Background: Macrophage activation syndrome (MAS) is a severe, potentially life-threatening complication of autoimmune diseases in children. Little is known about the association between MAS and the onset of juvenile systemic lupus erythematosus (jSLE). Objectives: The aim of this study was to determine the frequency and clinical features of MAS as the initial complication of jSLE. Methods: During 2004 and 2016, we retrospectively reviewed the clinical and laboratory features of 46 jSLE patients diagnosed at the Saitama Children's Medical Center. Patients who were complicated with MAS at the same time as jSLE. These patients were compared with a control group composed of jSLE patients without MAS. The MAS was diagnosed according to preliminary guidelines. Results: Fifteen patients (32.6%) developed MAS during the initial stage of jSLE. Fever, leukopenia, thrombocytopenia, hyperferritinemia hypofibrinogenemia, increased aspartate aminotransferase (AST), and increased lactate dehydrogenase (LDH) were more frequently observed in patients having jSLE with MAS than in those having jSLE without MAS. No differences were observed in serum C3 and C4 levels, or erythrocyte sedimentation rate (ESR) (P<0.05). Especially, Seven patients (46.7%) had neurologic symptoms that were significantly higher in those with MAS (P<0.01). All patients received corticosteroids when jSLE with MAS diagnosis was established, among whom seven received pulse methylprednisolone therapy. Two patients were treated with IVIG. Nine patients with MAS were treated with immunosuppressants, including cyclophosphamide and mycophenolate mofetil, azathioprine . No patient involved in this study died. Conclusions: MAS can be the initial manifestation of jSLE. MAS may be an underrecognized complication of jSLE. MAS with jSLE should be suspected in patients with high fever, cytopenia, and a liver disorder. In addition, we found that in jSLE with MAS patients, they had more neurologic symptoms compared to jSLE without MAS. Early diagnosis and intensive therapy is essential to improve the clinical outcome. References: Parodi A, Davì S, Pringe AB, Pistorio A, Ruperto N, et al. Macrophage activation syndrome in juvenile systemic lupus erythematosus: a multinational multicenter study of thirty-eight patients. Arthritis Rheum. 2009 Nov;60(11):3388–99. Pringe A, Trail L, Ruperto N, Buoncompagni A, Loy A, et al. Macrophage activation syndrome in juvenile systemic lupus erythematosus: an under-recognized complication? Lupus. 2007;16(8):587–92. Gormezano NW, Otsuzi CI, Barros DL, da Silva MA, Pereira RM, et al. Macrophage activation syndrome: A severe and frequent manifestation of acute pancreatitis in 362 childhood-onset compared to 1830 adult-onset systemic lupus erythematosus patients. Semin Arthritis Rheum. 2016 Jun;45(6):706–10. Disclosure of Interest: None declared